Same Personality, New Ways to Abuse: How Dark Tetrad Personalities Are Connected With Cyber Intimate Partner Violence - Pineda, David (Journal of interpersonal violence, 2022)
New technologies bring new forms of intimate partner violence (IPV) or abuse, such as cyber intimate partner violence (C-IPV). This is a contemporary issue with different consequences from in-person IPV. C-IPV is a complex phenomenon triggered by a number of factors, including personality traits such as the Dark Tetrad, composed of four ?malevolent? qualities: subclinical narcissism, Machiavellianism, subclinical psychopathy, and everyday sadism. The Dark Tetrad plays an important role in predicting the perpetration or victimization of the resulting pervasive behaviors. Although the correlations between in-person IPV and the Dark Tetrad have been studied before, to our knowledge this investigation is the first to look at the links between these four dark personality traits and C-IPV. With a sample of 1,189 participants, we measured C-IPV victimization and perpetration rates and compared the results with the Dark Tetrad profiles of the respondents. To analyze these correlations, we conducted bivariate analysis and structural equation modeling. The analysis yielded positive relations of psychopathy and narcissism with cyber controlling behaviors. Psychopathy was found to be strongly related with direct cyber aggression behaviors; sadism was mainly related with C-IPV victimization in both controlling and direct aggression, and, finally and interestingly, Machiavellianism presented negative correlations with direct cyber aggression. Remarkable is that joining sadistic personalities increased vulnerability to victimization from C-IPV direct aggression, as well as more psychopathic traits and an increased probability of perpetration. These combinations may create dangerous situations. In conclusion, we found that both C-IPV perpetrators and victims present higher scores in the dark personality traits and gender-based differences than in-person IPV actors.